1981
DOI: 10.1176/ajp.138.8.1115
|View full text |Cite
|
Sign up to set email alerts
|

Sympathoadrenomedullary hyperactivity in the neuroleptic malignant syndrome: a case report

Abstract: The authors describe a patient with the neuroleptic malignant syndrome whose excessive catecholamine excretion indicates hyperactivity of the sympathoadrenomedullary component of the autonomic nervous system. Their finding provides a physiological basis for using catecholamine blocking agents to treat some patients with this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…In our patient, 24-hour urinary catecholamine levels were markedly elevated, with norepinephrine excretion greater than 3.5 times the upper limit of normal (ULN), epinephrine excretion greater than 6.5 times ULN, and dopamine excretion greater than 2.3 times ULN. These results are in accordance with the increased urinary catecholamine and metanephrine values described in other case reports for both MC and NMS [2527]. …”
Section: Discussionsupporting
confidence: 93%
“…In our patient, 24-hour urinary catecholamine levels were markedly elevated, with norepinephrine excretion greater than 3.5 times the upper limit of normal (ULN), epinephrine excretion greater than 6.5 times ULN, and dopamine excretion greater than 2.3 times ULN. These results are in accordance with the increased urinary catecholamine and metanephrine values described in other case reports for both MC and NMS [2527]. …”
Section: Discussionsupporting
confidence: 93%
“…The findings in the present study cannot entirely explain the pathophysiology of malignant catatonia, but do indicate that hyperactivity of the sympathetic nervous system may be an important factor. Further, it is interesting to consider that previous studies have reported increased urine and plasma catecholamine levels in neuroleptic malignant syndrome 17,18. Although the data are insufficient to conclude that neuroleptic malignant syndrome and malignant catatonia are variants of the same disorder, these two disorders may be highly similar in terms of sympathetic nervous system hyperactivity.…”
Section: Discussionmentioning
confidence: 97%
“…The decreased levels of homovanillic acid, a CSF metabolite of dopamine, also supports this theory 18 . Other hypotheses are that sympathoadrenal dysfunction has a contributory role in NMS 19 , or a low serum iron concentration can be a contributory factor in decreasing the number of dopaminergic receptors, thereby leaving patients susceptible to developing NMS. This is supported by the finding of low serum iron in patients with NMS 20 .…”
Section: Discussionmentioning
confidence: 99%